RESEARCH ON THE TYPES AND STRUCTURE OF THE MAIN TYPES OF CONTAINERS USED IN THE TRANSPORT INDUSTRY - Akhmatov Navruz Bakhtiyorovich, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The main purpose of the work is to research the main types of containers used in rail transport. This article carried out analyzes of container types, their dimensions in standards and technical standards, and on the basis of this, the relevant information on the topic under consideration was determined. The importance of container transportation and the possibility of containerization infrastructure are presented in international and local transportation